2019
DOI: 10.32717/0131-0062-2018-64-50-59
|View full text |Cite
|
Sign up to set email alerts
|

Вплив Біогумусу На Ріст, Урожайність І Якість Часнику (Allium Sativum L.) В Умовах Правобережного Лісостепу України

Abstract: Аннотація. Характерною ознакою сучасного землеробства є погіршення родючості ґрунтів через їх інтенсивне використання, дефіцит водних ресурсів і, як наслідок, зниження продуктивності сільськогосподарського виробництва. Дані фактори визначають необхідність відновлення й підвищення родючості ґрунтів шляхом застосування у технології вирощування сільськогосподарських культур вермикомпосту (біогумусу), який є ефективним засобом відновлення родючості ґрунту, підвищення врожайності овочів та отримання органічної прод… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The highest yields were collected from the plots where the combined fertilisation with the biological product Phytohelp at a rate of 1 and 2 l/ha, foliar fertilisation with the mineral fertiliser Drip Fert N 15 P 5 K 30 +ME at a rate of 4 g/2 l of water and the bioadhesive Liposam at a rate of 1 l/ha were applied. O. Ulianych & V. Yatsenko (2018) found that the Sofiyivskyi garlic variety (multi-clove form) requires a maximum rate of biohumus of 5 t/ha, which increased the yield by 3.6 t/ha. For the Prometheus variety (small-toothed form), by increasing the weight of the tooth and increasing their number, the…”
Section: Discussionmentioning
confidence: 99%
“…The highest yields were collected from the plots where the combined fertilisation with the biological product Phytohelp at a rate of 1 and 2 l/ha, foliar fertilisation with the mineral fertiliser Drip Fert N 15 P 5 K 30 +ME at a rate of 4 g/2 l of water and the bioadhesive Liposam at a rate of 1 l/ha were applied. O. Ulianych & V. Yatsenko (2018) found that the Sofiyivskyi garlic variety (multi-clove form) requires a maximum rate of biohumus of 5 t/ha, which increased the yield by 3.6 t/ha. For the Prometheus variety (small-toothed form), by increasing the weight of the tooth and increasing their number, the…”
Section: Discussionmentioning
confidence: 99%